Correlation Between Benign Paroxysmal Positional Vertigo and 25-hydroxyvitamin D - Song, Penglong; Zhao, Xianshu; Xu, Yanjun; Zhao, Zhigang; Wang, Li; Liu, Yang; Gao, Qian (Frontiers in Neurology, 2020)
Objective: The correlation between benign paroxysmal positional vertigo (BPPV) and vitamin D levels was controversial. We explored age- and sex-related effects on 25-hydroxyvitamin D (25(OH)D) and correlation between 25(OH)D levels and BPPV. Subjects and Methods: We recruited 380 patients with BPPV and collected 25(OH)D records of 3125 control subjects who were further divided into age- and sex-based subgroups. We respectively investigated the effects of sex and age on 25(OH)D by comparing sex- or age-based subgroups. Then, we separately compared levels of 25(OH)D in sex-and age-based subgroups between the BPPV and control group. Results: 25(OH)D levels in male subgroups were significant higher than those in female subgroup both in the BPPV and control group. With increasing age, 25(OH)D levels gradually increased, and there were significant between-subgroup differences for age in the control group. In males, the significant between-subgroup difference was observed only in the <40 year subgroup. Three female age-matched subgroups (<40, 40–49 and 60–69) showed significant between-subgroup differences. Conclusions: There are sex and age differences in vitamin D levels. For both male and female patients with BPPV aged <40 years and female patients with BPPV aged 40–49 and 60–69 years, the lower vitamin D level is a risk factor for BPPV. In female patients with BPPV aged 50–59 and >70 years, and male patients with BPPV aged >40 years, the correlation between vitamin D and BPPV is non-existent.